E-readiness of ODL multicultural lecturers: Implications for effective mediation - Nyoni, Jabulani (South African Journal of Higher Education, 2016)
This article is a narrative report of the findings from the analysis of multicultural facilitators discourses on their e-readiness in the use of information and communication technologies (ICTs) affordances in open and distance learning (ODL) mediation experiences. Firstly findings revealed by qualitative deconstructive discourse analysis (DDA) indicated that the majority of ODL facilitators/instructors lack e-readiness skills that are critical in the effective manipulation of ICT affordances in teaching and learning in ODL environments. Secondly some facilitators did not fully understand what undergirds ODL pedagogy, principles and practices. The institutions academic lecturers are periodically given e-training but this seems to be inadequate. I argue that a comprehensive orientation tutorial package covering e-readiness, e-training and ODL principles and practices should be organised for all inexperienced as well as newly employed lecturers to appropriately prepare them for the rigors of ODL pedagogy.